2019
DOI: 10.1016/j.neuroimage.2019.116052
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state connectivity reveals a role for sensorimotor systems in vocal emotional processing in children

Abstract: Voices are a primary source of emotional information in everyday interactions. Being able to process non-verbal vocal emotional cues, namely those embedded in speech prosody, impacts on our behavior and communication. Extant research has delineated the role of temporal and inferior frontal brain regions for vocal emotional processing. A growing number of studies also suggest the involvement of the motor system, but little is known about such potential involvement. Using resting-state fMRI, we ask if the patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

6
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 92 publications
5
22
0
Order By: Relevance
“…This is comparable to previous studies on the correlates of individual differences in emotion recognition (e.g. [48][49][50]). Table 2 shows zero-order correlations between mindfulness and the remaining study variables.…”
Section: Discussionsupporting
confidence: 90%
“…This is comparable to previous studies on the correlates of individual differences in emotion recognition (e.g. [48][49][50]). Table 2 shows zero-order correlations between mindfulness and the remaining study variables.…”
Section: Discussionsupporting
confidence: 90%
“…Such associations are often causally attributed to training (Schellenberg, 2019), however, and the current study shows that similar advantages can be In exploratory analyses, we found that participants reporting higher singing abilities were also better at recognizing emotions in speech prosody. This finding implies that other facets of musical expertise are involved in associations with vocal emotions, and is consistent with well-documented behavioral and neural links between production, imagery, and perceptual mechanisms in voice processing (Correia et al, 2019;Lima et al, 2015;Lima, Krishnan, & Scott, 2016;McGettigan et al, 2015;Pfordresher & Halpern, 2013;Warren et al, 2006). On the one hand, vocal production (such as singing) involves not only implementing movements but also planning and anticipating outcomes (which might rely on imagery), and using auditory feedback (perceptual processes) to detect and correct errors.…”
Section: Discussionsupporting
confidence: 87%
“…Each task included 60 trials, with 10 different stimuli for each of the six emotional categories (anger, disgust, fear, happiness, sadness, and neutrality). The stimuli were part of previously validated corpora (speech prosody, Castro & Lima, 2010; nonverbal vocalisations, Lima et al, 2013a; facial expressions, Karolinska Directed Emotional Faces database, Goeleven et al, 2008) that have been frequently used (e.g., Agnoli et al, 2012; Correia et al, 2019, 2020; Lima & Castro, 2011; Lima et al, 2016; Lima et al, 2013b; Safar & Moulson, 2020). Speech prosody stimuli were short sentences ( M = 1473 ms, SD = 255) with emotionally neutral semantic content (e.g., “O quadro está na parede”, The painting is on the wall), produced by two female speakers to communicate emotions with prosodic cues alone.…”
Section: Methodsmentioning
confidence: 99%